Investment attractiveness of the Russian manufacturing industry under sanctions and restrictions - M. A. Korkin (Вестник университета)
The effective industrial development in Russian industry plays a leading role in the country’s economy. The article is devoted to the study of the direction of effective investment in the Russian industry at the present stage of economic development, in particular manufacturing. The purpose of the study is to assess the volume of investments of the Russian manufacturing industry in difficult conditions of re-equipment and reconfiguration of production processes for import substitution. The dynamics of manufacturing industries in various areas of production in the country is considered. The factors that have a positive and negative impact on the effective development of the Russian manufacturing industry in recent years have been identified. Based on the conducted research, a general conclusion is formulated that it is expedient for the country to make investments for the effective development of the manufacturing industry.